Hepatic metastasis of a parathyroid carcinoma treated with intra-arterial embolization (2017)
This paper reports the case of a patient with parathyroid carcinoma and metastatic parathyroid carcinoma in the liver, as well as persistent hypercalcemia resistant to the management with zoledronic acid and cinacalcet.The patient was treated with intra-arterial embolization using polyvinyl alcohol microspheres in the right hepatic artery, achieving an excellent biochemical control after the intervention.